2012
DOI: 10.1039/c2jm30897e
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photodynamic selectivity of nano-silica-attached porphyrins against breast cancer cells

Abstract: The synthesis and characterization of bare silica (4 nm in diameter) nanoparticle-attached meso-tetra(N-methyl-4-pyridyl)porphine (SiO2-TMPyP, 6 nm in diameter) are described for pH-controllable photosensitization. Distinguished from organosilanes, SiO2 nanoparticles were functionalized as a potential quencher of triplet TMPyP and/or singlet oxygen (1O2) at alkaline pH, thereby turning off sensitizer photoactivity. In weak acidic solutions, TMPyP was released from SiO2 surface for efficient production of 1O2. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…A plethora of porphyrin derivatives have been extensively studied due to their fascinating photophysical and electrochemical properties [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Intrinsically, porphyrins are biogenic molecules responsible for various biological processes such as photosynthesis and respiration [19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A plethora of porphyrin derivatives have been extensively studied due to their fascinating photophysical and electrochemical properties [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Intrinsically, porphyrins are biogenic molecules responsible for various biological processes such as photosynthesis and respiration [19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Intrinsically, porphyrins are biogenic molecules responsible for various biological processes such as photosynthesis and respiration [19][20][21][22][23][24][25][26][27][28][29]. Porphyrins have wide applications in solar energy harvesting and artificial photosynthesis [7][8][9][12][13][14][15][16][30][31][32], industrial processes as catalysts [1][2][3][4]6,[33][34][35], photodynamic therapy [11,17,36], anticancer pharmaceutical drugs [10] and photodynamic destruction of viruses [5,37]. Therefore, knowledge on the solvent dependent photophysical properties of porphyrin molecules is extremely important for designing molecular devices of medical, bio-medical and environmental importance.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al reported the synthesis of silica nanoparticles with TMPyP attached [86]. Their results indicated that while in an alkaline pH environment the silica particles quench the TMPyP 1 O 2 production, in weak acidic solutions (characteristic of tumor environments) TMPyP is released and ROS production is recovered.…”
Section: Nanoparticle-mediated Delivery Of Photosensitizersmentioning
confidence: 99%
“…One material that may prove useful in combining a dual imaging and therapy is mesoporous silica NPs; with their large surface areas and pore volumes, one or two modalities (optical imaging agent and an anticancer drug) can be incorporated into the silica matrix while loading the other modality into its pores. [509][510][511] Encapsulating drug payloads in NPs can prevent exposure of healthy cells to the cytotoxic drug and may prove more beneficial (e.g., lower toxicity and fewer side effects) at lower doses than the free drug. However, this can reveal much more complex than the use of simple small-molecule drugs that are easily characterized.…”
Section: Perspectives: Multimodal Theranostic Npsmentioning
confidence: 99%